Efficacy of newer insecticides against sucking insect pests of groundnut (Arachis hypogaea L.): EFFICACY OF NEWER INSECTICIDES AGAINST SUCKING INSECT PESTS OF GROUNDNUT - M VENKATAIAH; B ANILKUMAR; SREEDHAR CHAUHAN (Journal of Oilseeds Research, 2016)
A field study was conducted at Regional Agricultural Research Station, Polasa, Jagtial, Karimnagar district, Telangana State during rabi/summer season of 2010-11 and 2011-12 to evaluate the efficacy of newer insecticides along with conventional insecticides against sucking pests viz., thrips and leafhoppers in groundnut. The results revealed that buprofezin 25SC @ 500 ml/ha and fipronil 5SC 1000 ml/ha were found to be effective and recorded lowest mean per cent leaf damage due to the sucking pests in groundnut as compared to untreated control. The insecticides were also recorded higher dry pod yield as compared to other insecticides and untreated control.